2019
DOI: 10.35940/ijeat.a1146.1291s419
|View full text |Cite
|
Sign up to set email alerts
|

Coelomic Fluid of Earthworm, Eudrilus Eugeniae, Inhibits the Growth of Fungal Hyphae, in Vitro

Abstract: Knowledge on interactions between earthworms and microbes at molecular level has been obscure. Mechanism by which earthworms defend themselves against different microorganisms in the soil is largely unknown. Coelomic fluid from earthworm species has been shown to have antimicrobial activity. In this study we report that coelomic fluid isolated from Eudrilus eugeniae has antifungal activity against four different phytopathogens such as Rhizoctonia solani, Fusarium oxysporum, Aspergillus flavus and Verticillium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In their habitat, which has rich microbiota and ensures constant contact between microorganisms and earthworms, these animals have evolved mechanisms preventing development of illnesses 18 – 21 . The most popular formulations made from earthworms are powders and pastes 20 – 24 . It has been evidenced that coelomic fluid is rich in proteins, enzymes, peptides, and polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their habitat, which has rich microbiota and ensures constant contact between microorganisms and earthworms, these animals have evolved mechanisms preventing development of illnesses 18 – 21 . The most popular formulations made from earthworms are powders and pastes 20 – 24 . It has been evidenced that coelomic fluid is rich in proteins, enzymes, peptides, and polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…It has fibrinolytic properties, exerts vasorelaxant effects, and has beneficial properties for the liver 17 , 18 , 22 . Earthworm preparations have documented antibacterial and antifungal properties 20 , 21 , 24 28 . Current research has demonstrated that coelomic fluid has anticancer activity against HeLa, A549, Pa17, PC-12, or Hep-2 cancer cell lines 20 , 26 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the living environment of earthworms is rich in fungal organisms, fungi are the main source of food for earthworms 7 and at the same time, these invertebrates have mechanisms protecting them against pathogenic species. One of them is the action of the coelomic fluid (CF), which has been proven to kill fungal cells 8 . CF secreted by the dorsal pores contains many bioactive compounds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…such enzymes as proteases 9 11 , lysozymes 12 , 13 , metalloenzymes 14 , and fibrinolytic enzymes 15 as well as polysaccharides 16 , proteins 17 19 , and nutrients, etc. These factors have antibacterial 20 , 21 , antifungal 8 , 22 , anti-inflammatory 23 , antioxidant 23 , 24 , and anticancer 10 , 11 , 25 27 effects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relationship between the central nervous system and the social ability of earthworm suggested its application towards research on social interaction (Gopi Daisy et al 2016). Coelomic uid of earthworms was demonstrated to inhibit the growth of fungal hyphae in vitro (Plavšin et al 2017;Rajesh et al 2019). Besides, coelomic uid of earthworm species Eudrilus eugeniae has been shown to promote seed germination and the growth of legume seedling (Nadana Raja Vadivu et al 2019).…”
Section: Introductionmentioning
confidence: 99%